UPAYA MENINGKATKAN PEMAHAMAN SISWA KELAS III SDN HARMONI KECAMATAN CAMPAKA TENTANG KETAATAN KEPADA TUHAN YANG MAHA ESA MELALUI PENDEKATAN KONTEKSTUAL DALAM PEMBELAJARAN PAI - Amaliyah, Siska; Rianti, Rini (Dirasa Islamiyya: Journal of Islamic Studies, 2024)
In Islamic Religious Education (PAI) learning, the contextual approach method is applied to enhance students' understanding of obedience to God the Almighty. Over time, the author observed a decline in students' obedience levels, which is partly caused by the negative influence of technology. This influence has made students lazy in performing religious activities and often postponing obligations such as prayer, which affects their obedience to Allah SWT. This observation prompted the author to conduct research aimed at improving students' understanding of obedience through the application of the contextual approach in PAI learning in grade III of SDN Harmoni, Campaka District. This study uses a qualitative method with a case study approach, employing data collection techniques such as participant observation and the collection of student works. The collected data was analyzed qualitatively using qualitative data analysis techniques. The research findings show that the application of the contextual approach in PAI learning is effective in improving students' understanding of obedience, including examples of obedience and how to apply it in daily life. This study is expected to provide valuable contributions to enhancing students' understanding of obedience to God the Almighty and the development of more effective PAI teaching methods.